2015
DOI: 10.3892/ol.2015.3711
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative/antioxidative enzyme-mediated antiproliferative and proapoptotic effects of the GPER1 agonist G-1 on lung cancer cells

Abstract: Abstract. Estrogen mediates fast signal responses or transcriptional events via G protein-coupled estrogen receptor 1 (GPER1). However, there is no data on the effect of GPER1 on lung cancer cell proliferation and apoptosis. The present study aimed to analyze the anticancer effects of the GPER1 agonist G-1 on A549 human lung cancer cells. A549 cells were treated with 17β-estradiol and G-1, and cell proliferation was analyzed using MTT and WST assays. In addition, the apoptotic effects induced by G-1 were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
(35 reference statements)
2
15
0
Order By: Relevance
“…Compounds 4a and 4b were synthesized from reaction between 2-amino-thiophenol with chalcones 3a and 3b in ethanol at reflux (10 h) in good yield (Table I). All spectral data of compounds 4a and 4b ( 1 H NMR, 13 C NMR, IR, elemental analysis) corresponded with the proposed structures.…”
Section: Chemistrysupporting
confidence: 64%
See 1 more Smart Citation
“…Compounds 4a and 4b were synthesized from reaction between 2-amino-thiophenol with chalcones 3a and 3b in ethanol at reflux (10 h) in good yield (Table I). All spectral data of compounds 4a and 4b ( 1 H NMR, 13 C NMR, IR, elemental analysis) corresponded with the proposed structures.…”
Section: Chemistrysupporting
confidence: 64%
“…PANC-1 cells were obtained from the American Tissue Culture Collection (Manassas, VA, USA). Cells were cultured as described previously (13). In brief, cells were cultured in high glucose Dulbecco's modified Eagles medium (DMEM) (Gibco Life Technologies, Carlsbad, CA, USA) supplemented with 100 U/ml penicillin (Sigma-Aldrich, St. Louis, MO, USA) and 10% fetal bovine serum (FBS; Gibco Life Technologies) at 37˚C in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, GPER mediates the proliferative effect of estrogen in numerous cancer types . Accordingly, GPER agonist G‐1 was shown to inhibit tumor growth in triple‐negative breast cancer cells, adrenocortical carcinoma, lung cancer, and ovarian cancer…”
Section: Introductionmentioning
confidence: 99%
“…effect of estrogen in numerous cancer types. 9,10 Accordingly, GPER agonist G-1 was shown to inhibit tumor growth in triple-negative breast cancer cells, 11 adrenocortical carcinoma, 12 lung cancer, 13 and ovarian cancer. 14 TAM is considered as an ER antagonist and GPER agonist, 15,16 which has been the first-line targeted therapy for the management of ER positive breast cancers for almost 60 years.…”
mentioning
confidence: 99%
“…However, accumulating evidence indicated that G-1 is a potent tumor growth inhibitor. Recent studies demonstrated that G-1 suppresses proliferation and induces apoptosis in numerous types of cancer cells, including: ovarian cancer (911), adrenocortical carcinoma (12), Lung cancer (13), cervical cancer (14), and prostate cancer (15). …”
Section: Introductionmentioning
confidence: 99%